Unveiling the Vital Role of Trade Secrets in Sustaining Culinary Businesses for MSMEs - Thalib, Nur Aisyah; Dibah, Nabilah Farah; Riswandi, Budi Agus (Universitas Internasional Batam, 2024)
This article explores the critical role of trade secrets in enhancing the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector. It emphasizes the confidential nature of corporate information, essential for shielding against unauthorized access by the public or even employees. Given the significant economic value of Indonesia's local products, legal safeguards are imperative to protect these assets from unfair competitive practices in the market. Utilizing a normative juridical method, this study conducts a comprehensive literature review to investigate the legal framework surrounding trade secrets and its implications for MSMEs. The findings underscore a prevalent lack of awareness among MSMEs regarding intellectual property laws, highlighting the necessity for concerted efforts from various stakeholders to ensure effective implementation of these legal protections.